Perancangan Sistem Pakar Diagnosa Penyakit Lupus Eritmatosus Sistem(LES) Dengan Metode Forward Chaining Menggunakan Pemrograman PHP dan MySQL - novi yona sidratul munti (JURNAL FASILKOM (teknologi inFormASi dan ILmu KOMputer), 2019)
The research objective is to design and build a web-based expert software engineering system that is able to diagnose Lupus Erythematosus System (LES) in humans to get solutions and information easily and quickly. The results shown are in the form of user conditions related to Lupus Eritmatosus System (LES). The results are also complemented with a description of the disease and treatment solutions that are displayed in the form of a website using PHP programming with a MySQL database. The conclusion of this research is that the PHP and MySQL programming languages ​​are proven to be able to be implemented in engineering expert systems to diagnose the Lupus Erythmatosus System (LES). The fordward chaining method is proven capable of tracing the symptoms of Lupus Erythmatosus System (LES) easily and quickly. The online system can help users get information about the types of diseases, symptoms and treatment solutions in the disease Lupus Erythmatosus System (LES) .